Avaliação do clima organizacional como ferramenta de gestão na Universidade Federal de Santa Maria - Fighera, Andressa (2017)
The present study aimed to propose the implementation of an organizational climate assessment process appropriate to the context of the Federal University of Santa Maria (UFSM). In order to do so, six models of organizational climate assessment were studied, reaching Rizzatti's model (2002) as the most appropriate to the context of a public educational institution. Thus, an instrument of organizational climate assessment adapted from the author was applied to 399 (three hundred and ninety nine) UFSM servers. The results, based on the analysis of the variables contemplated, and the analysis of the influence of the profile of the participants in the evaluation of the organizational climate, enabled the presentation of a diagnosis referring to the organizational climate in the UFSM, which, in general, can be considered positive. Sequentially, through the exploratory factorial analysis, it was possible to adjust the research instrument, which remained composed by the variables: Institutional Image; Human Resources Policies; System of Assistance and Benefits; Organizational Structure; Organization and Working Conditions; Interpersonal Relationship; Behavior of Managers, Personal Satisfaction and Single (flexible) work shift. Thus, it was possible to propose a complete methodology of evaluation of organizational climate for the Federal University of Santa Maria.